PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL PROBLEM BASED LEARNING (PBL) MATERI BANGUN RUANG SISI DATAR PADA SISWA KELAS VIII SMP MUDER TERESA - Simon Seli Tokan; Uke Ralmugiz; St. Muthmainnah Yusuf (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2023)
Development of Learning Devices Using a Problem Based Learning (PBL) Model for Building Flat Sided Spaces for Class VIII Students of Muder Teresa Middle School for the2020/2021 Academic Year. Thesis for the Mathematics Education Study Program, FKIP, Muhammadyah University, Kupang. This study aims to produce learning tools in the form of lesson plans and worksheets on flat sided geometric shapes using a problem-based learning model for class VIII students of SMP Muder Teresa Kupang who have valid, practical and effective qualifications. This research is development research using the modified ADDIE model which includes analysis, design, development, implementation, and evaluation with 10 respondents. The data collection technique used was lesson plan assessment sheets, LKS assessment sheets and tests. To test the validity of the data, practicality, and effectiveness used analytical techniques. Based on the results of the analysis, it is known that the development of mathematics learning tools using a problembased learning model to improve the ability and independence of learning mathematics for Grade VIII students of SMP Muder Teresa, Kupang, is feasible to use.